Applications of Wild Isolates of Saccharomyces Yeast for Industrial Fermentation: The Gut of Social Insects as Niche for Yeast Hybrids’ Production - Di Paola, Monica; Meriggi, Niccolò; Cavalieri, Duccio (Frontiers in Microbiology, 2020)
In the industry of fermented food and beverages, yeast cultures are often selected and standardized in order to ensure a better control of fermentation and a more stable product over time. Several studies have shown that the organoleptic characteristics of fermented products reflect geographic variations of the microbial community composition. Despite investigations of the worldwide distribution and genetic diversity of Saccharomyces cerevisiae, it is still unclear how and to what extent human intervention has shaped the brewer’s yeast population structure. The genotypic and phenotypic characterization of environmental yeast populations and their potential application in the fermentative processes can significantly enrich the industrial fermentation products. Social insects have proven to be closely associated to the yeasts ecology. The relationships between yeasts and insects represent a fundamental aspect for understanding the ecological and evolutionary forces shaping their adaptation to different niches. Studies on phylogenetic relationships of S. cerevisiae populations showed genetic differences among strains isolated from gut and non-gut environments (i.e., natural sources and fermentation). Recent evidences showed that insect’s gut is a reservoir and an evolutionary niche for Saccharomyces, contributing to its survival and evolution, favoring its dispersion, mating and improving the inter-specific hybrids production during hibernation. Here, we discuss the potential use of social insects for production of a wide range of hybrid yeasts from environmental Saccharomyces isolates suitable for industrial and biotechnological applications.